(untitled) (Research, Society and Development, 2023)
Objective: To verify the importance of nursing care in the clinical management of women with breast cancer. Methodology: This study is an integrative literature review, using the PubMed and Bireme databases. All available studies were used, studies published between 2019 and 2023, in Portuguese, Spanish and English, with the following descriptors: Breast cancer; Early diagnosis; Risk factors; Nursing care. Results: 678 studies were identified, of which 477 were excluded based on the exclusion criteria. Based on the title and abstract, 201 studies were evaluated and 45 studies were eligible for the full text reading stage. For this integrative review, 8 studies were included. Discussion: It has been shown that nurses are important in the clinical management of women with breast cancer, and are essential for care that ranges from diagnosis to treatment and rehabilitation of the patient. Final considerations: it can be concluded that integrating the family into the treatment of palliative cancer patients is a strategy to promote comfort for the patients and their families. For this reason, we can see the importance of professional nurses during cancer treatment, in order to meet the needs of terminal cancer patients and their caregivers.